2x+3(x-4)=-7+5x-5

Simple and best practice solution for 2x+3(x-4)=-7+5x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(x-4)=-7+5x-5 equation:



2x+3(x-4)=-7+5x-5
We move all terms to the left:
2x+3(x-4)-(-7+5x-5)=0
We add all the numbers together, and all the variables
2x+3(x-4)-(5x-12)=0
We multiply parentheses
2x+3x-(5x-12)-12=0
We get rid of parentheses
2x+3x-5x+12-12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| -8-3x=11———2 | | -5m=-60 | | 3/18=7/x | | 1900=35x+125 | | (2x-17)=(3x-18) | | 85(z−6)=−15(2z+3) | | 8p–40=32 p= | | 5(x-2)-7x=32 | | 5(6+x)=13x+9 | | a+2.9=1.9 | | 2m-7-11m=-13m+5 | | 5/t=75/165 | | 27=9-n | | (10x+8)/2=5x+4 | | 1/6(18x-12)=10x-8 | | 6(1+4n)+1=175 | | 2(x-3)=4-3(x+4) | | 65=2x=6x+9 | | 10^{x}=800 | | (4x-6)/2=-7 | | z/18=8/12 | | 7=x8 | | 5x+-3=28 | | 5y-10=1+5y+9 | | 5x-8=12x+76 | | F(2)=6x+4 | | 8x+11=12x-17 | | 7x+4=31+4x | | -2(3x-4)=2x+20-2x+6 | | –5u4u=–4. | | r/16=27 | | 10n-5=23 |

Equations solver categories